Architectural heritage value with indigenous culture in Binh Duong (in case of the architecture of traditional houses and communal house) - Tran Dinh Hieu; Nguyen Quoc Truc (Tạp chí Khoa học và Công nghệ)
Binh Duong territory has a long history marked typically by an architectural culture of Vietnamese, French, Chinese style. This land has an open village structure that was established through royal bibliographies and directories in the early stages of Nguyen Dynasty. People of Southeast region have an open spirit and cultural exchanges with Chinese; Therefore, they have created their own cultural and architectural character through the way of their treating of Gods in architecture of communal houses. At the end of 16th, 17th and middle 18th centuries, because of dissatisfaction of some Vietnamese population from Central provinces with Trinh Nguyen Lord war, migrating of valet members of Nguyen Lord to Southern territory and with French colonial period formed architectural culture system of traditional architecture and colony style. The contents analyze, evaluate cultural and architectural values of typical communal houses and traditional houses through cultural and architectural characteristics of typical heritage buildings.